Low-thermal-conductivity thermal insulation material as well as preparation method and application thereof
By impregnating polystyrene foam with an infrared-visible light reflecting solution, the thermal conductivity of insulation materials is reduced, addressing the issue of thick walls in ultra-low energy buildings and optimizing living space.
Patent Information
- Application Number
- CN202411605289.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-31
AI Technical Summary
Polystyrene foam insulation boards used in ultra-low energy buildings require thick insulation layers due to their thermal conductivity above 0.03 W/(m·K), occupying excessive building area and reducing living space.
A low thermal conductivity insulation material is prepared by immersing polystyrene foam in an infrared-visible light reflecting impregnation liquid under vacuum and normal pressure, followed by drying, utilizing materials like tetraethyl orthosilicate and barium sulfate to reduce thermal conductivity.
The thermal conductivity of the polystyrene foam board is reduced below 0.03 W/(m·K), minimizing the thickness of insulation layers and preserving living space in ultra-low energy buildings.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of building wall insulation boards, and in particular to a low thermal conductivity insulation material, a preparation method and an application thereof. Background Art
[0002] Building facilities consume a lot of energy for heating in winter and cooling in summer. Ultra-low energy buildings can reduce the demand for building heating and air conditioning to the greatest extent through reasonable design, significantly improve the efficiency of energy equipment and systems through active technical measures, and provide a comfortable indoor environment with less energy consumption. This is an effective measure to reduce my country's total energy consumption. In building energy consumption, the heat loss of building exterior walls accounts for a very large proportion. Therefore, building exterior wall insulation technology and its energy-saving materials have become the focus of ultra-low energy building development. At present, commonly used wall insulation materials include aluminum silicate insulation materials, phenolic foam materials, polystyrene foam materials, inorganic insulation mortars, etc. Among them, polystyrene foam insulation materials have the characteristics of low density, good thermal conductivity, excellent mechanical properties, chemical corrosion resistance, easy processing, and convenient construction, and have become the mainstream exterior wall insulation materials.
[0003] The main technical problem at present is that although polystyrene foam insulation boards already have good thermal insulation properties, their thermal conductivity is usually above 0.03W / (m·K). If traditional polystyrene foam insulation boards are used to build ultra-low energy buildings, a very thick insulation layer is required to meet the "Passive Ultra-Low Energy Residential Building Energy Saving Design Standard" DB13(J) / T8359-2020. This will result in the exterior walls of most of the current ultra-low energy buildings occupying a large amount of building area, and the corresponding actual living area of people will be reduced. Therefore, it is an important issue at present to develop an insulation material with better thermal conductivity and reduce the thickness of the building insulation layer. Summary of the invention
[0004] In view of the technical problems existing in the prior art, the present invention aims to provide a low thermal conductivity thermal insulation material, a preparation method and an application thereof.
[0005] One of the purposes of the present invention is to provide a method for preparing a low thermal conductivity heat-insulating material, the preparation method comprising: In a vacuum environment, the polystyrene foam insulation material is completely immersed in the infrared-visible light reflecting impregnation liquid, and after vacuum impregnation, it is impregnated at normal pressure, and then taken out and dried to obtain the low thermal conductivity insulation material.
[0006] Preferably, the vacuum impregnation time is 20 to 40 minutes, and the normal pressure impregnation time is 5 to 20 minutes.
[0007] Preferably, the infrared-visible light reflecting immersion liquid comprises raw materials of the following components: Base resin 60%-70% Infrared-visible light reflector 20%-30% Titanium dioxide 5%-10% Anti-settling agent 1%-2% Defoaming agent 1%-2%, or Silane coupling agent 1%-2%.
[0008] Preferably, the method for preparing the infrared-visible light reflecting immersion liquid comprises: The base resin, infrared-visible light reflector, titanium dioxide, anti-settling agent, defoamer and silane coupling agent are mixed evenly, and then the vacuum is released after stirring for 20 to 40 minutes under vacuum to obtain an infrared-visible light reflective impregnation solution.
[0009] Preferably, the matrix resin includes one or more of phenolic resin, urea-formaldehyde resin or melamine resin; Preferably, the titanium dioxide comprises rutile titanium dioxide; Preferably, the anti-settling agent comprises BYK-405 and / or BYK-410; Preferably, the defoamer comprises a phenolic resin defoamer; Preferably, the silane coupling agent includes KH560 and / or KH550.
[0010] Preferably, the preparation method of the infrared-visible light reflector comprises: S1: mixing tetraethyl orthosilicate, ethanol and water and dispersing them to obtain a tetraethyl orthosilicate ethanol solution; mixing barium sulfate, ethanol and water and dispersing them to obtain a barium sulfate ethanol solution; S2 Add the ethyl orthosilicate ethanol solution dropwise into the barium sulfate ethanol solution at room temperature, raise the temperature to 70-90°C, adjust the pH to 8-10, and stir the reaction for 1-3 hours; After the reaction in S3 is completed, the solid and liquid are separated, and the solid is dried and ground into powder; S4 calcines the powder at 300-500°C for 5-6 hours to obtain an infrared-visible light reflector.
[0011] Preferably, the content of ethyl orthosilicate in the infrared-visible light reflector is 20-30%.
[0012] Preferably, the mass ratio of tetraethyl orthosilicate, ethanol and water is 1:2:1; the mass ratio of barium sulfate, ethanol and water is 1:2:1.
[0013] A second object of the present invention is to provide a low thermal conductivity heat insulation material.
[0014] The third object of the present invention is to provide a low thermal conductivity insulation material for use in ultra-low energy consumption building walls.
[0015] Beneficial effects of the present invention: The present invention prepares an infrared-visible light reflector by compounding tetraethyl orthosilicate and barium sulfate, and prepares the compound into an impregnating liquid with infrared-visible light reflective function. Then, through an impregnation production process, the impregnating liquid with infrared-visible light reflective function is infiltrated into the interior of a polystyrene foam insulation material to prepare a low thermal conductivity insulation material, thereby greatly reducing the thermal conductivity of the polystyrene foam board and controlling its thermal conductivity to be below 0.03W / (m·K), thereby solving the problem of too thick walls and reduced housing area during the construction of ultra-low energy consumption buildings. DETAILED DESCRIPTION
[0016] According to the first aspect of the present invention, a method for preparing a low thermal conductivity heat insulation material is provided, the preparation method comprising: In a vacuum environment, the polystyrene foam insulation material is completely immersed in the infrared-visible light reflecting impregnation liquid, and after vacuum impregnation, it is impregnated at normal pressure, and then taken out and dried to obtain the low thermal conductivity insulation material.
[0017] In the present invention, when heat is transferred in the form of infrared radiation inside the material, it will be reflected back when it encounters the infrared-visible light reflecting material, rather than directly penetrating the material. This reduces the heat transfer in the form of infrared radiation and reduces the overall thermal conductivity of the material. For the visible light part, the infrared-visible light reflecting material can also play a reflective role. The energy carried by visible light will also be converted into heat to a certain extent. When the visible light is reflected, the visible light energy entering the material is reduced, thereby reducing the heat converted by the visible light and reducing the thermal conductivity of the material.
[0018] In the present invention, after the impregnation liquid penetrates into the interior of the polystyrene foam insulation board, it will fill the pores of the polystyrene material. The polystyrene foam itself has many tiny pores, and air usually exists in these pores. The thermal conductivity of air is relatively low, which is one of the reasons why the polystyrene foam insulation board has certain thermal insulation performance. After the impregnation liquid enters the pores, it changes the structure and gas flow state in the pores, and also hinders the convection movement of the air in the pores. Gas convection is a way of heat transfer. When gas convection is hindered, the heat transfer in this way will also be reduced. Just like in a closed space, if the air cannot flow, it is difficult for heat to be transferred to other areas through air convection, thereby reducing the overall thermal conductivity of the material.
[0019] There is an interface between the infrared-visible light reflective material and the polystyrene matrix. During the heat transfer process, when heat is transferred from the polystyrene matrix to the reflective material, or from the reflective material back to the polystyrene matrix, thermal resistance will be generated at the interface. This interfacial thermal resistance will hinder the smooth transfer of heat, making the heat transfer process hindered and requiring more energy to pass through the interface, thereby increasing the overall thermal resistance.
[0020] The infrared-visible light reflective material is evenly distributed inside the polystyrene foam insulation board, making the heat conduction path inside the material more tortuous and complicated. Heat needs to bypass these particles to continue to transfer, which lengthens the heat conduction path. According to the principle of heat conduction, the longer the conduction path, the more difficult it is to transfer heat and the lower the thermal conductivity.
[0021] In a preferred embodiment of the present invention, the vacuum impregnation time is 20 to 40 minutes, and the normal pressure impregnation time is 5 to 20 minutes.
[0022] In a preferred embodiment of the present invention, the infrared-visible light reflecting immersion liquid comprises raw materials of the following components: Base resin 60%-70% Infrared-visible light reflector 20%-30% Titanium dioxide 5%-10% Anti-settling agent 1%-2% Defoaming agent 1%-2%, or Silane coupling agent 1%-2%.
[0023] The preparation method of the infrared-visible light reflecting immersion liquid comprises: In a preferred embodiment of the present invention, the base resin, infrared-visible light reflector, titanium dioxide, anti-settling agent, defoamer and silane coupling agent are mixed evenly, stirred under vacuum for 20 to 40 minutes and then released to obtain an infrared-visible light reflective impregnation solution.
[0024] In a preferred embodiment of the present invention, the base resin includes one or more of phenolic resin, urea-formaldehyde resin or melamine resin; Preferably, the titanium dioxide comprises rutile titanium dioxide; Preferably, the anti-settling agent comprises BYK-405 and / or BYK-410; Preferably, the defoamer comprises a phenolic resin defoamer; Preferably, the silane coupling agent includes KH560 and / or KH550.
[0025] In a preferred embodiment of the present invention, the preparation method of the infrared-visible light reflector comprises: S1: mixing tetraethyl orthosilicate, ethanol and water and dispersing them to obtain a tetraethyl orthosilicate ethanol solution; mixing barium sulfate, ethanol and water and dispersing them to obtain a barium sulfate ethanol solution; S2 Add the ethyl orthosilicate ethanol solution dropwise into the barium sulfate ethanol solution at room temperature, raise the temperature to 70-90°C, adjust the pH to 8-10, and stir the reaction for 1-3 hours; After the reaction in S3 is completed, the solid and liquid are separated, and the solid is dried and ground into powder; S4 calcines the powder at 300-500°C for 5-6 hours to obtain an infrared-visible light reflector.
[0026] In the present invention, the tetraethyl orthosilicate in the infrared-visible light reflector generates silicon dioxide after the above reaction. Silicon dioxide has a lower refractive index and thermal conductivity, and a higher emissivity, and has a higher radiation effect on both visible light and near-infrared light. Barium sulfate has the characteristics of a wide electronic band gap, a high refractive index and a low solar absorption rate, and is an important thermal insulation filler.
[0027] In a preferred embodiment of the present invention, the content of ethyl orthosilicate in the infrared-visible light reflector is 20-30%.
[0028] In a preferred embodiment of the present invention, the mass ratio of tetraethyl orthosilicate, ethanol and water is 1:2:1; the mass ratio of barium sulfate, ethanol and water is 1:2:1.
[0029] In the present invention, the preparation method of the low thermal conductivity heat insulation material specifically includes: First prepare the infrared-visible light reflector: A certain amount of tetraethyl orthosilicate, ethanol and water are mixed, and dispersed for 5 to 20 minutes using an ultrasonic disperser to obtain a tetraethyl orthosilicate ethanol solution, wherein the mass ratio of tetraethyl orthosilicate, ethanol and water is 1:2:1; A certain amount of barium sulfate, ethanol and water are mixed and dispersed by ultrasonic disperser for 5 to 20 minutes to obtain a barium sulfate ethanol solution, wherein the mass ratio of barium sulfate, ethanol and water is 1:2:1; At room temperature, add the ethyl orthosilicate ethanol solution dropwise to the barium sulfate solution in a flask with a stirring device, and the final amount of ethyl orthosilicate added to the solution is 20%-30%. After the addition is completed, the reaction temperature is raised to 70-90°C, and an appropriate amount of ammonia water is added to adjust the pH to 8-10, and the reaction is stirred for 1-3 hours.
[0030] After the reaction is completed, the solid and liquid are separated by suction filtration, and the solid filter cake is washed 3 times with ethanol. Finally, the filter cake is placed in a blast drying oven at 40-50°C for 1-3 hours. After the filter cake is dried, it is taken out and ground into powder. The powder is calcined at 300-500°C for 5-6 hours using a muffle furnace to obtain an infrared-visible light reflector.
[0031] Then prepare the infrared-visible light reflecting immersion liquid: Weigh a certain amount of base resin, then add infrared-visible light reflector, titanium dioxide, anti-settling agent, defoamer and silane coupling agent, and use a high-speed disperser to disperse for 3-10 minutes at a speed of 1000r / min. After dispersion, put the impregnation liquid into a vacuum stirring kettle with a stirring device and perform vacuum treatment. The vacuum stirring time is 20-40 minutes. After the vacuum stirring is completed, release the vacuum to obtain the impregnation liquid.
[0032] Finally, prepare the low thermal conductivity insulation material: In a vacuum environment, the polystyrene foam insulation material is completely immersed in the infrared-visible light reflecting impregnation liquid with a vacuum pressure of -0.09~-0.08 MPa for 20~40 minutes. After the impregnation is completed, the vacuum is released for 10~20 minutes. After the vacuum is released to normal pressure, the insulation material is taken out after continuing to be immersed for 5~15 minutes and its surface is wiped. The impregnated insulation board is placed in a drying oven at 30~60℃ and dried for 24~36 hours to obtain an ultra-low energy consumption insulation board for building walls.
[0033] According to a second aspect of the present invention, a low thermal conductivity heat insulation material is provided.
[0034] According to the third aspect of the present invention, there is provided an application of a low thermal conductivity insulation material in ultra-low energy consumption building walls.
[0035] Example The preparation method of the low thermal conductivity insulation material is as follows: First prepare the infrared-visible light reflector: A certain amount of tetraethyl orthosilicate, ethanol and water are mixed, and then dispersed for 10 minutes using an ultrasonic disperser to obtain a tetraethyl orthosilicate ethanol solution, wherein the mass ratio of tetraethyl orthosilicate, ethanol and water is 1:2:1; A certain amount of barium sulfate, ethanol and water were mixed, and then dispersed for 10 minutes using an ultrasonic disperser to obtain a barium sulfate ethanol solution, wherein the mass ratio of barium sulfate, ethanol and water was 1:2:1; At room temperature, add the ethyl orthosilicate ethanol solution dropwise to the barium sulfate solution in a flask with a stirring device, and the final amount of ethyl orthosilicate added to the solution is 20%-30%. After the addition is completed, the reaction temperature is raised to 80°C, and an appropriate amount of ammonia water is added to adjust the pH to 9, and the reaction is stirred for 2 hours.
[0036] After the reaction is completed, the solid and liquid are separated by suction filtration, and the solid filter cake is washed with ethanol three times. Finally, the filter cake is placed in a 45°C forced air drying oven for 2 hours. After the filter cake is dried, it is taken out and ground into powder. The powder is calcined at 400°C for 5-6 hours in a muffle furnace to obtain an infrared-visible light reflector.
[0037] The models of infrared-visible light reflectors prepared with different contents of ethyl orthosilicate are shown in Table 1:
[0038] Then prepare the infrared-visible light reflecting immersion liquid: Weigh a certain amount of base resin, then add infrared-visible light reflector, titanium dioxide, anti-settling agent, defoamer and silane coupling agent, and disperse them in a high-speed disperser for 5 minutes at a speed of 1000r / min. After dispersion, put the impregnation liquid into a vacuum stirring kettle with a stirring device and perform vacuum treatment. The vacuum stirring time is 30 minutes. After the vacuum stirring is completed, release the vacuum to obtain the impregnation liquid.
[0039] The present invention provides 8 embodiments, and Table 2 shows the raw material ratios of the impregnation solutions of Embodiments 1 to 6 and Comparative Examples 1 to 2. In Embodiments 1 to 6 and Comparative Examples 1 to 2, the infrared-visible light reflector is IR-VIS2, the base resin is phenolic resin, the titanium dioxide is rutile titanium dioxide, the anti-settling agent is BYK-410, the defoamer is phenolic resin defoamer DJ-260, and the silane coupling agent is KH560.
[0040] The raw material proportions of the impregnation solutions of Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Table 2.
[0041] Table 2 Ratio of raw materials in Examples 1 to 6
[0042] Example 7 The infrared-visible light reflector model selected is IR-VIS1, and the rest is the same as in Example 2.
[0043] Example 8 The infrared-visible light reflector model selected is IR-VIS3, and the rest is the same as in Example 2.
[0044] Finally, prepare the low thermal conductivity insulation material: In a vacuum environment, the polystyrene foam insulation material is completely immersed in the infrared-visible light reflecting impregnation liquid in the above embodiments and comparative examples, the vacuum pressure is -0.09~-0.08 MPa, the vacuum impregnation is 30 minutes, the vacuum is released after the impregnation is completed, the release time is 15 minutes, after the vacuum is released to normal pressure, the insulation material is taken out after continuing to be immersed for 5~15 minutes, and its surface is wiped; the impregnated insulation material is placed in a drying oven at 50°C and dried for 48 hours to obtain an ultra-low energy consumption building wall insulation material.
[0045] Performance Testing Testing standard: GB / T10295-2008 Table 3 Thermal conductivity test results of Examples 1 to 8 and Comparative Examples 1 to 2
Claims
1. A method for preparing a low thermal conductivity heat insulation material, characterized in that: The preparation method comprises: In a vacuum environment, the polystyrene foam insulation material is completely immersed in the infrared-visible light reflecting impregnation liquid, and after vacuum impregnation, it is impregnated at normal pressure, and then taken out and dried to obtain the low thermal conductivity insulation material.
2. The preparation method according to claim 1, characterized in that The vacuum impregnation time is 20 to 40 minutes, and the normal pressure impregnation time is 5 to 20 minutes.
3. The preparation method according to claim 1, characterized in that: The infrared-visible light reflecting immersion liquid comprises the following raw materials: Base resin 60%-70% Infrared-visible light reflector 20%-30% Titanium dioxide 5%-10% Anti-settling agent 1%-2% Defoaming agent 1%-2%, or Silane coupling agent 1%-2%.
4. The preparation method according to claim 1, characterized in that: The preparation method of the infrared-visible light reflecting immersion liquid comprises: The base resin, infrared-visible light reflector, titanium dioxide, anti-settling agent, defoamer and silane coupling agent are mixed evenly, and then the vacuum is released after stirring for 20 to 40 minutes under vacuum to obtain an infrared-visible light reflective impregnation solution.
5. The preparation method according to claim 3, characterized in that: The base resin includes one or more of phenolic resin, urea-formaldehyde resin or melamine resin; Preferably, the titanium dioxide comprises rutile titanium dioxide; Preferably, the anti-settling agent comprises BYK-405 and / or BYK-410; Preferably, the defoamer comprises a phenolic resin defoamer; Preferably, the silane coupling agent includes KH560 and / or KH550.
6. The preparation method according to claim 3, characterized in that: The preparation method of the infrared-visible light reflector comprises: S1: mixing tetraethyl orthosilicate, ethanol and water and dispersing them to obtain a tetraethyl orthosilicate ethanol solution; mixing barium sulfate, ethanol and water and dispersing them to obtain a barium sulfate ethanol solution; S2 Add the ethyl orthosilicate ethanol solution dropwise into the barium sulfate ethanol solution at room temperature, raise the temperature to 70-90°C, adjust the pH to 8-10, and stir the reaction for 1-3 hours; After the reaction in S3 is completed, the solid and liquid are separated, and the solid is dried and ground into powder; S4 calcines the powder at 300-500°C for 5-6 hours to obtain an infrared-visible light reflector.
7. The preparation method according to claim 6, characterized in that: The content of ethyl orthosilicate in the infrared-visible light reflector is 20-30%.
8. The preparation method according to claim 6, characterized in that: The mass ratio of tetraethyl orthosilicate, ethanol and water is 1:2:1; the mass ratio of barium sulfate, ethanol and water is 1:2:
1.
9. A low thermal conductivity heat-insulating material obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the low thermal conductivity insulation material according to claim 9 in ultra-low energy consumption building walls.